Organizational commitment, group-leader relations and turnover intention: a study of local marketing officers in securities firms owned by foreign interests in Hong Kong - Sit, Kenneth Y. S. (Curtin University, 2003)
Employee turnover is important to individuals; organizations and society. From an individual’s perspective, turnover can have both potentially positive and negative consequences not just on himself or herself, but also on his or her family members and those who remain with the organization, irrespective of whether they are close associates with the person who has decided to leave the organization. From the organizational perspective, employee turnover can be costly - time and effort on loss recruitment, training, socialization investments, disruption, etc. From the societal perspective, turnover can bring in significant consequences which include mobility and migration to new industries and organizations for economic development. This study focuses on the relationship between one of the antecedents of organizational commitment – group/leader relations and the turnover intention of local marketing officers in securities firms owned by foreign interests in Hong Kong. Various studies have shown that the antecedents of organizational commitment such as personal traits, job characteristics, group and leader relations and company attributes are related to the turnover intention of staff but not much of it has been done in Hong Kong. The primary objective of this study is to propose a parsimonious model to address the issue of employee withdrawal among a sample of marketing executives working in foreign securities firms in Hong Kong SAR. The research design is quantitative in nature, testing various hypotheses on two levels of exchange within organizations - between subordinate and organization and between subordinate and supervisor. Factors involved in the first category of exchange – subordinate/organization are referred to as organizational factors and those in the second category (subordinate/supervisor) as supervisory factors.These factors were regressed against turnover intention to establish their role in the employee withdrawal process. Organization commitment was then introduced into the model as a mediating variable and results on further regression of the organizational and supervisory factors against turnover intention were noted. Before organizational commitment was introduced as a mediating variable, all the hypotheses with the exception of leader participation were rejected. When organizational commitment was introduced as a mediating variable on the regression of turnover intention on organizational and supervisory constructs, all of the hypotheses with the exception of group cohesiveness and leader participation were rejected. While the results seemed to lend some support to the postulation on the important role played by organizational commitment and group/leader relations in the employee withdrawal process, more studies must be carried out to substantiate the findings. Directions on future study were discussed and managerial implications for both practitioners and researchers were suggested.